Revisores/as - Psicología, Actualidades en (Universidad de Costa Rica, 2020)
Alejandra Stein, Universidad de Buenos Aires, Argentina Benjamín Reyes Fernández, Universidad de Costa Rica, Costa Rica Cesar Núñez, Universidad de Medellín, Colombia David Torres, Universidad de Iberoamérica, Costa Rica Felipe Biasus, Universidade Federal de Santa Catarina, Brasil John Alejandro Sanín Posada, Centro de Investigación en Comportamiento Organizacional Cincel, Colombia Juan Pardo-Montero, Instituto de Investigación Sanitaria de Santiago, España Karen Tautiva Ochoa, Universidad del Rosario, Colombia Lucía Inmaculada Llinares-Insa, Universidad de Valencia, España Luis Manuel Lozano, Universidad de Granada, España Luis Valero Aguayo, Universidad de Málaga, España María Ángeles Pastor, Universidad Miguel Hernández de Elche, España Marina Rezende Bazon, Universidade de São Paulo, Brasil Mónica Roncancio, Universidad Pontificia Bolivariana, Colombia Nairan Ramirez-Esparza, University of Connecticut, EEUU Perla Trejo Ortiz, Universidad Politécnica de Zacatecas, México Rodrigo Ardiles Irarrázabal, Universidad de Antofagasta, Chile Santiago Resett, Consejo Nacional De Investigaciones Científicas y Técnicas, Argentina